A Method of Security Emergency Plan Decision Making by Cloud Model Computing. Issue 4 (February 2020) - Yin, Hang; Feng, Chaoying
Abstract: This paper designed a method of security emergency plan decision making by cloud model computing. This method is made in order to accurately determine security emergency plan in time when safety accident occurred. First, built a index system which is suitable for comprehensive transportation projects. Second, ran a cycle improvement rate according to cloud thickness to get the evaluation indexes and cloud weight, and then put them into the comprehensive formula to get the reference cloud. At last, drew reference cloud and evaluation clouds on a 3D picture by Matlab and compare each evaluation cloud with the reference cloud, the plan which had the finest similarity is the best one. This method can realize visual comparison for safety emergency plans.